"Power of Storytelling": A Content Analysis of Chronic Pain Narratives on YouTube. Issue 1 (1st January 2021) - Devan, Hemakumar; Elphick-laveta, Toa; Lynch, Maxwell; MacDonell, Katie; Marshall, David; Tuhi, Leah; Grainger, Rebecca
ABSTRACT: Background : First-person digital narratives are short videos produced independently by or in partnership with the person to tell their personal experience. Objectives : The objective of this study was to describe how first-person digital narratives of adults with non-cancer pain are represented on YouTube. A secondary aim was to analyze first-person digital narratives hosted on pain management websites of professional organizations to explore whether these videos represented chronic pain with the same content. Method : Guided by the methodological framework of Arksey and O'Malley, a conventional content analysis was undertaken analyzing the chronic pain videos published on YouTube and six global pain management websites. Results : Of the 78 videos (54 YouTube and 24 pain websites) that were analyzed, the overarching theme "power of storytelling" suggests that personal stories were used as a medium to share lived experiences of chronic pain, providing help and advice to similar others. The four supporting themes were (1) My pain journey, (2) Navigating health care, (3) Pain and the impact on me, and (4) What works for me. There was no major difference in subthemes between the YouTube and pain website videos. Conclusion : Digital narratives enable those living with chronic pain to voice their experiences and communicate their pain journeys and may thus provide a sense of validation. Digital narratives can be used as a therapeutic tool to provide insights for others into the lived experience of chronic pain and to provide peer support for people with pain. Future studies are needed to investigate the clinical effectiveness and implementation of digital stories in chronic pain management.